2011
DOI: 10.1039/c1pp05058c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium chloride on the binding of polyaromatic hydrocarbon guests with sodium cholate aggregates

Abstract: Sodium cholate aggregates are adaptable host systems. The effect of changing the ionic strength with the addition of NaCl on the properties for guest binding to sodium cholate aggregates was investigated by using pyrene, perylene and 1-ethylnaphthalene as guests. Fluorescence, anisotropy and laser flash photolysis studies provided information on the protection efficiency of the aggregate bound guest, and provided information on the dynamics and correlation times for the host-guest system. Different trends for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(62 citation statements)
references
References 66 publications
9
51
0
Order By: Relevance
“…Therefore, an inflection point is observed at the CMC in the plot of the ratio I I /I III when pyrene experiences a change from the hydrophilic environment to the hydrophobic environment in the core of the micelle. 19 In the presence of 1 M NaCl, the I I /I III ratio of pyrene is decreased from 0.843 to 0.702 in the case of sodium cholate (NaCh) aggregates 19 and the decrease is mainly due to the decreased contact between aggregate bound pyrene and the water molecules close to the aggregates. However, with increasing concentration of bile salts the size of the aggregate is increased and therefore, the CMC value of the aggregate is broader than that of conventional surfactants.…”
Section: Pyrene (Py) Fluorescence Within [Bmim]-bf 4 Added Aqueous Namentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, an inflection point is observed at the CMC in the plot of the ratio I I /I III when pyrene experiences a change from the hydrophilic environment to the hydrophobic environment in the core of the micelle. 19 In the presence of 1 M NaCl, the I I /I III ratio of pyrene is decreased from 0.843 to 0.702 in the case of sodium cholate (NaCh) aggregates 19 and the decrease is mainly due to the decreased contact between aggregate bound pyrene and the water molecules close to the aggregates. However, with increasing concentration of bile salts the size of the aggregate is increased and therefore, the CMC value of the aggregate is broader than that of conventional surfactants.…”
Section: Pyrene (Py) Fluorescence Within [Bmim]-bf 4 Added Aqueous Namentioning
confidence: 99%
“…19 Thus, an increase in the I I /I III ratio for the Py bound NaDC aggregate from 0.7 in the absence of [bmim]-BF 4 to 1.03 in the presence of 9.8 wt% [bmim]-BF 4 (0.43 M) suggests that a significant increase occurs in the polarity of the NaDC binding sites, and the behavior of the IL correlates well with organic cosolvents, where the water accessibility to the binding sites of the aggregates is increased with the addition of cosolvents and upon performing control experiments it can also be concluded that in the presence of a high concentration of IL, pyrene does not relocate itself to the [bmim]-BF 4 aggregates or to the water medium. 19 Thus, an increase in the I I /I III ratio for the Py bound NaDC aggregate from 0.7 in the absence of [bmim]-BF 4 to 1.03 in the presence of 9.8 wt% [bmim]-BF 4 (0.43 M) suggests that a significant increase occurs in the polarity of the NaDC binding sites, and the behavior of the IL correlates well with organic cosolvents, where the water accessibility to the binding sites of the aggregates is increased with the addition of cosolvents and upon performing control experiments it can also be concluded that in the presence of a high concentration of IL, pyrene does not relocate itself to the [bmim]-BF 4 aggregates or to the water medium.…”
Section: Pyrene (Py) Fluorescence Within [Bmim]-bf 4 Added Aqueous Namentioning
confidence: 99%
See 3 more Smart Citations